A new method for measuring the static and dynamic fabric/garment drape using 3D printed mannequin. Issue 6 (3rd June 2022) - Issa, Marwa; Elgholmy, Sherwet; Sheta, Aida; Fors, M. Nashat
Abstract: The study aims to develop a cloth drapemeter using a three-dimensional (3 D) printed mannequin, where drape can be measured for both the static and dynamic states. The modification achieved in the new drapemeter gives researchers the ability to test the fabric and/or the garment for the static and dynamic drapes, using one instrument. Methodology: Other factors affecting the garment drape could also be tested at low fabric consumption since the mannequin is scaled (i.e. smaller than the size of the human body). Also, a comparison between the real and virtual skirts was performed, to test the effectiveness of the virtual method. Digital photos were taken for the actual fabric/garment on the drapemeter, as well as those of the virtually designed skirts. They were analyzed using an image processing software, to study the drape behavior and factors affecting it. Results: From this study, the increasing number of seam lines led to a reduction in the draped area, while increasing the angle of the skirt depending on its design raised it. Also, the draped area increased by the increment of the rotation speed of the disk of the drapemeter. It could be concluded that the developed apparatus is recommended to be commercially used in predicting the fabric and garment drape, in the static and dynamic cases. Another conclusion was that the virtually designed skirts were different from the actual skirts.